THE INFLUENCE OF VIDEO-BASED LEARNING MEDIA (AUDIO-VISUAL) ON THE LEARNING EFFECTIVENESS OF STUDENTS IN JUNIOR HIGH SCHOOL - A D W Limbong; B O Panjaitan; M W Silitonga; N F Ginting (ISER (Indonesian Science Education Research), 2021)
This study aims to see the effect of video-based media on junior high school student learning activities and the effect of using video-based media on junior high school student learning outcomes. The study complied with health protocols using online quantitative quantitative methods via Google Form and in person interviews with several teachers via WhatsApp. The population in this study were junior high school teachers and junior high school students. The results showed that there was a significant effect of the use of video-based learning media on student learning activities, there was a significant effect of using video-based learning media on learning outcomes